A visual LISP program for voxelizing AutoCAD solid models. (January 2015) - Marschallinger, Robert; Jandrisevits, Carmen; Zobl, Fritz
Abstract: AutoCAD solid models are increasingly recognized in geological and geotechnical 3D modeling. In order to bridge the currently existing gap between AutoCAD solid models and the grid modeling realm, a Visual LISP program is presented that converts AutoCAD solid models into voxel arrays. Acad2Vox voxelizer works on a 3d -model that is made up of arbitrary non-overlapping 3D-solids. After definition of the target voxel array geometry, 3D-solids are scanned at grid positions and properties are streamed to an ASCII output file. Acad2Vox has a novel voxelization strategy that combines a hierarchical reduction of sampling dimensionality with an innovative use of AutoCAD-specific methods for a fast and memory-saving operation. Acad2Vox provides georeferenced, voxelized analogs of 3D design data that can act as regions-of-interest in later geostatistical modeling and simulation. TheSupplement includes sample geological solid models with instructions for practical work with Acad2Vox. Graphical abstract: Highlights: Acad2Vox converts arbitrary AutoCAD 3D-solids to 3D grid data. It follows a novel, CAD-oriented and efficient voxelization strategy. Multiple AutoCAD versions are supported.